Suspected involvement of fentanyl in prior overdoses and engagement in harm reduction practices among young adults who use drugs. Issue 4 (2nd October 2019) - Goldman, Jacqueline E.; Krieger, Maxwell S.; Buxton, Jane A.; Lysyshyn, Mark; Sherman, Susan G.; Green, Traci C.; Bernstein, Edward; Hadland, Scott E.; Marshall, Brandon D. L.
Abstract: Background: From 2011 to 2016, the United States has experienced a 55% increase in overall overdose deaths and a 260% increase in fatal fentanyl-related overdoses. Increasing engagement in harm reduction practices is essential to reducing the rate of fentanyl-related overdoses. This study sought to examine the uptake of harm reduction practices among young adults who reported recent drug use and who were recruited for a study to assess the utility and acceptability of rapid fentanyl test strips. Methods: Between May and October 2017, 93 young adults who reported drug use in the past 30 days were recruited through word of mouth, Internet advertising, and public canvasing. Participants completed an interviewer-administered survey that assessed participants' sociodemographic and behavioral characteristics, suspected fentanyl exposure, and overdose history. We assessed harm reduction practices and other correlates associated with experiencing a suspected fentanyl-related overdose. Results: Of 93 eligible participants, 36% ( n = 34) reported ever having experienced an overdose, among whom 53% ( n = 18) suspected having experienced a fentanyl-related overdose. Participants who had ever experienced a fentanyl-related overdose were more likely to keep naloxone nearby when using drugs compared with those who had never experienced an overdose and those who had experienced an overdose that they did not suspect was related to fentanyl ( P < .001). Additionally, experiencing a suspected fentanyl-related overdose was associated with having previously administered naloxone to someone else experiencing an overdose ( P < .001). Conclusion: Those who had experienced a suspected fentanyl-related overdose were more likely to carry and administer naloxone. Future overdose prevention interventions should involve persons who have experienced a suspected fentanyl overdose and/or responded to an overdose in order to develop harm reduction programs that meet the needs of those at risk of an overdose.